41.8k views
5 votes
The question is in the photo. Complete C and D.

The question is in the photo. Complete C and D.-example-1
User Rbacarin
by
6.2k points

2 Answers

1 vote
What they said ☝️ x = -12
User Pwnosaurus
by
7.2k points
6 votes

Answer:

x = -12

Explanations:

Given the following equation


-(1)/(2)x=6

We are to find the variable x. To do that, we will multiply both sides by -2 as shown:


\begin{gathered} -(1)/(2)x*-2=6*-2 \\ x=6*-2 \\ x=-12 \end{gathered}

This shows that the value of x for the equation to be true is -12

Check

If x = -12, on substiituting;


\begin{gathered} =-(1)/(2)(-12) \\ =(-12)/(-2) \\ =\text{ 6} \end{gathered}

Since the result is equivalent to 6, this shows that the solution x = -12 is correct.

User Nadapez
by
5.2k points